Expressive Speech Acts Fostering Social Harmony In Tulo Village Interpersonal Conversations: Tindak Tutur Ekspresif Pembentuk Keharmonisan Sosial Dalam Percakapan Interpersonal Desa Tulo - Rossa Nur Ramadhani; Idris Patekkai; Julia Marfuah; Ulinsa Ulinsa; Arum Pujiningtyas (Universitas Muhammadiyah Sidoarjo, 2026)
General Background Language serves as a crucial pragmatic tool for human communication and societal interaction. Specific Background Expressive utterances specifically function to communicate a speaker's psychological attitude toward various daily situations. Knowledge Gap While previous pragmatic studies extensively explore language in formal contexts, media, and literature, natural conversational dynamics within rural communities remain largely undocumented. Aims This qualitative descriptive study aims to describe the forms and functions of expressive speech acts within everyday community conversations in Tulo Village. Results Observational and conversational data analysis reveals five primary forms of psychological expressions: thanking, congratulating, apologizing, blaming, and praising. The dominant occurrence of apologizing signifies a community characterized by active efforts to preserve societal relationships and resolve communication discomfort. Functional applications include expressing gratitude, offering appreciation, conveying regret, and delivering constructive criticism. Novelty This research provides distinct empirical documentation of localized pragmatic characteristics in Tulo Village, shifting the analytical focus from formal discourse to authentic rural interactions. Implications These findings demonstrate the critical role of linguistic politeness in maintaining relationship cohesion, offering a foundational reference for understanding culturally responsive pragmatic frameworks. Highlights The pragmatic analysis identifies apologizing as the most dominant linguistic behavior. Residents frequently utilize thanking, congratulating, praising, and blaming to convey psychological attitudes. These communicative strategies actively resolve interactional discomfort and sustain polite relationships. Keywords Pragmatics; Expressive Speech Acts; Linguistic Politeness; Psychological Attitudes; Rural Communication